Children and Young People Presenting in a Pediatric Emergency Department in North-West England in Suicidal Crisis: An Exploratory Case Series Study - Ashworth, Emma; Provazza, Serena; McCarthy, Molly; Saini, Pooja (Frontiers in Psychiatry, 2022)
Suicide is a leading cause of death among children and young people (CYP) worldwide, and rates have been increasing in recent years. However, while evidence exists regarding factors associated with suicide and self-harm, there is limited information publicly available on the CYP who present in suicidal crisis. This is a case series study of CYP (aged 8-16) experiencing suicidal crisis who presented in an Emergency Department at a paediatric hospital in North-West England between March 2019 and March 2021 (n = 240). Clinical records were extracted and audited to explore demographic data, methods of recording patient attendance, the clinical pathways available and the patterns of pathway usage, and differences in CYP presentations before and after the COVID-19 pandemic. Attendees were mostly White females, with a mean age of 13.5 years, and 24% had a diagnosed special educational need. ‘Social/social problems’ was the most commonly used code for recording attendance (38%), and pathways varied depending on code used. A range of parental and familial factors were also identified. There were more CYP presenting with self-harm in addition to suicide ideation after the pandemic began (43% vs 27% pre-pandemic). This study provides the first clear insight into CYP who seek help at a North-West Emergency Department for suicidal crisis, and work is now needed to develop effective prevention strategies tailored towards the groups most at-risk.